2017
DOI: 10.26603/ijspt20171057
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Accuracy of the Lever Sign for Detecting Anterior Cruciate Ligament Injury

Abstract: Background: An alternative physical examination procedure for evaluating the integrity of the anterior cruciate ligament (ACL) has been proposed in the literature but has not been validated in a broad population of patients with a symptomatic complaint of knee pain for its diagnostic value.Purpose: To investigate the diagnostic accuracy of the Lever Sign to detect ACL tears and compare the results to Lachman testing in both supine and prone positions.Study design: Prospective, blinded, diagnostic accuracy stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
40
2
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 16 publications
0
40
2
5
Order By: Relevance
“…In comparison, the Lachman test had values of 65% and 100%, respectively. 11 Jarbo et al found the sensitivity and specificity for the lever sign test to be 63% and 90%, respectively. 3 They found the values for the Lachman test to be 90% and 96%.…”
Section: Summary Of Search Best Evidence Appraised and Key Findingsmentioning
confidence: 99%
See 4 more Smart Citations
“…In comparison, the Lachman test had values of 65% and 100%, respectively. 11 Jarbo et al found the sensitivity and specificity for the lever sign test to be 63% and 90%, respectively. 3 They found the values for the Lachman test to be 90% and 96%.…”
Section: Summary Of Search Best Evidence Appraised and Key Findingsmentioning
confidence: 99%
“…3,11,12 The included studies compared the sensitivity and specificity values for the lever sign test and the Lachman test. 3,11,12 One study 11 included cohorts of patients under anesthesia when the tests were administered, and the others had cohorts of awake patients. 3,12 Jarbo et al compared results of the tests to the reference standard of MRI.…”
Section: Summary Of Search Best Evidence Appraised and Key Findingsmentioning
confidence: 99%
See 3 more Smart Citations